COLOUR COMPONENT IN THE SEMANTICS OF ETHNOPHOBIC TERMS (the case of non-standard American English) - Ihor Honta; Tatiana Pastushenko; Nataliia Borysenko (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2019)
The study aimed to identify the semantic and structural characteristics of ethnophobic terms with a colour component, as well as the conceptual basis and extralinguistic factors that have a role in their formation. Ethnophobic terms tend to emerge in the non-standard language, with slang making its core. Although often marked as derogatory or impolite, ethnicity-laden slang expressions form a dynamic and productive part of non-standard vocabulary, largely due to their pragmatic power. Ethnophobic terms used with reference to the largest ethnic minorities in the USA (Black, Latin and Native Americans) became the focus of our research. Given their prototypical nature and a wide spectrum of connotations, basic colour terms have shown the highest potential for integration with the ethnicity concept: an overwhelming number of ethnophobic terms contain explicit or implicit colour components in their semantic structure encoding the following colour categories: black, brown, red, yellow, and white. We have also suggested that in American ethnophobic slang, the universal opposition of black and white may have transformed into a conceptual opposition of "white" vs. "non-white" that has a variety of verbal representations. In addition, semantic configuration and evaluative power of colour categories are determined by the speaker's point of reference affected by the stereotypes dominating their ethnic groups. Data analysis has shown that the morphological means of word formation typical of ethnophobic terms, including suffixation, compounding, blending, and abbreviation, are mainly combined with metonymy, metaphor, or both.